High-quality transesophageal echocardiography - Linker, David T. (Academic Press, 2022)
"High-Quality Transesophageal Echocardiographypresents a step-by-step approach aimed to help readers understand how to perform a high-quality transesophageal echocardiogram. The book explains the steps, tips, tricks, and troubleshooting tactics for performing a transesophageal echocardiogram effectively and with highest diagnostic utility, while ensuring patient safety and comfort."